2019
DOI: 10.25000/acem.454426
|View full text |Cite
|
Sign up to set email alerts
|

Changes in incidence and age distribution of scabies: A retrospective cohort study in a tertiary hospital

Abstract: Aim: Scabies is a pruritic skin disease caused by an ectoparasite named sarcoptes scabies var hominis. It sometimes makes endemics depending on lifestyles of communities. In this study, we point out that patients with scabies have increased in recent years. Methods: A retrospective review was carried out in the patients with scabies diagnosis between 2013January and 2018 July at the dermatology outpatient clinic of Karabuk Research and Training Hospital. The age and gender of the patients, and the season of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Likewise, in the study of Anderson and Strowd [1], the mean age of the cases with scabies was detected as 27 years. In addition, we also found that the mean age of patients with scabies has decreased significantly over the years, similar to the study of Aktaş et al [7]. Although scabies occurs in both genders, while some researches indicate that it is dominant among males, others show that it is more common among females [8].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Likewise, in the study of Anderson and Strowd [1], the mean age of the cases with scabies was detected as 27 years. In addition, we also found that the mean age of patients with scabies has decreased significantly over the years, similar to the study of Aktaş et al [7]. Although scabies occurs in both genders, while some researches indicate that it is dominant among males, others show that it is more common among females [8].…”
Section: Discussionsupporting
confidence: 87%
“…In the retrospective study covering the period between 2006-2017 conducted by Çetinkaya et al [6] in Kayseri the number of cases per population was at the highest level in 2014. In the retrospective cohort study covering the period 2013-2017 which was conducted by Aktaş et al [7] in Karabük, the scabies was determined to increase progressively. In our study, it was determined that the number of cases with scabies between 2010-2013 was below 0.26% and it increased by 3.5 times in 2014 compared to the previous year and exceeded 0.9%, and this progress continued in the following years.…”
Section: Discussionmentioning
confidence: 99%
“…In studies reported from our country in recent years, it has been reported that the incidence of scabies has got an increasing trend (9,10). Besides, we found that the increase in the frequency of scabies encountered in outpatient clinics in the 4 th quarter of the last year gained momentum and increased from 0.42% to 1.54% from 2017 to 2019 (5).…”
Section: Discussionmentioning
confidence: 54%
“…It was observed that most of the patients in this study were treated with sulfur ointment (60.5%). It is noteworthy that the patients who received treatment with sulfur ointments to younger ages from 2013 to 2018 (11). No difference was observed in the distribution of scabies prevalence according to different ages from 2014 to 2019 in a recent multicentre study conducted in distinct regions of Turkey (12).…”
Section: Discussionmentioning
confidence: 93%
“…In the literature, there were both female and male dominance observed in various studies investigating scabies (10)(11)(12). The population and geographical differences in the studies may explain the contradictory results.…”
Section: Discussionmentioning
confidence: 99%